A nona‐band narrow‐frame antenna with a defected ground structure for mobile phone applications. Issue 1 (8th October 2019) - Pang, Jiarui; Zhu, Mingmin; Yu, Guoliang; Zhou, Haomiao
Abstract: A nona‐band narrow‐frame antenna with a defected ground structure for mobile phone applications is presented in this article. From the analysis of the structure, the coupled‐fed antenna mainly consists of four parts: bending feeding strip, coupling shorted strip, copper plate and defected ground structure. It can effectively cover LTE700/GSM850/GSM900/DCS1800/PCS1900/UMTS2100/LTE2300/LTE2500 and the ninth band on 3300‐4200 MHz (including LTE3500), which may be applied to the future 5G. The size of the nona‐band antenna is 80 × 7.5 × 5 mm 3, and the defected ground structure is only 55 × 0.5 mm 2 . This structure effectively widens the bandwidth of the low‐frequency band and realizes 2G/3G/4G and possible coverage of the 5G operating band without loading the lumped elements. Thus, it is suitable for smartphone application. A prototype of the proposed antenna is manufactured and measured. The measured −6 dB impedance band‐widths in the low, mid and high bands are 340 MHz (630‐970 MHz), 1410 MHz (1510‐2920 MHz) and 1060 MHz (3160‐4220 MHz), respectively. In addition, the efficiency of the antenna is greater than 60% in most of the working frequency bands, and the antenna has good radiation performances.